Sistemas de salud y subsidios a los pobres: un modelo de financiamiento de salud para el Perú - Vera, José Carlos (2004)
This research develops a financing model for public health services that establishes the health expenditure per person that the State would have to pay according to the package of services it wishes to offer and the population it decides to subsidize. With this objective, it proposes a health insurance system for the entire population, in which the State contributes all or part of the value of the corresponding premiums to the population with the fewest resources, thus replacing the subsidy to the offer —which it currently provides— by the subsidy to the demand, which means freedom of choice of the user as regards both the insurance entity and the service provider. The actuarial financial analysis is used for the necessary calculations, which is based on an analysis of the health situation and the transactions of services in the market in terms of their financial consequences. One of its main findings is to confirm that the problem of health in Peru is not the lack of resources, but the way in which the health sector and the subsidy system have been structured.